The contested role of foreign and domestic foundations in the PRC: policies, positions, paradigms, power - Fulda, Andreas (British Association for Chinese Studies, 2017)
This research paper examines how foundations—foreign and domestic, public and private, operating and grant making engage with Chinese civil society organisations in an authoritarian political context. In contrast to previous literature, which considers civil society through the lens of state-society relations, the author contends that in the case of China, civil society-building has been a foundation-led process. Following a discussion of conceptual caveats in the nascent field of foundation research, the author traces how China’s evolving policy framework has influenced the development trajectories, legal statuses and modes of operation of both foreign and domestic foundations. The empirical part of the paper focuses on foundation positions, paradigms and power. Based on 12 in-depth interviews conducted in 2014 with foundation representatives and CSO leaders, this research reveals how foreign and domestic foundations position themselves vis-à vis the party-state, market and civil society; how they understand philanthropy; and how they deal with the power imbalance in the relationship between grant maker and grantee. Research findings show that foundations have different value propositions, visions and missions, as well as different theories of change, which determine their philanthropic approaches. Foreign and domestic foundation representatives primarily follow a paradigm of conventional charity, managerial philanthropy, or political philanthropy. Findings from this research raise a number of pertinent questions about the likely impacts of China’s controversial Overseas NGO Law on foreign and domestic foundations and their grantees.